Main Clinical Features of COVID-19 and Potential Prognostic and Therapeutic Value of the Microbiota in SARS-CoV-2 Infections - He, Yu; Wang, Jianhui; Li, Fang; Shi, Yuan (Frontiers in Microbiology, 2020)
Recently, a novel coronavirus SARS-CoV-2 has caused Coronavirus Disease 2019(COVID-19) outbreak in the world with more than 150,000 patients infected. Here, we generally describe the character of SARS-CoV-2 and COVID-19. SARS-CoV-2 shared 79.5% identical sequence with SARS-CoV and uses the same receptor angiotensin-converting enzyme2 (ACE2). The distribution of ACE2 may help us to understand the movement route of SARS-CoV-2 in the respiratory tract, blood, and digestive system. The clinical features of COVID-19 are similar to severe acute respiratory syndrome(SARS) while it is estimated the fatality of COVID-19 would be much lower(1.5-2.5% VS about 10%). The relationship between SARS-CoV-2 and microbiota needs to be explored for its potential role in the aid of diagnosis and treatment. Enrichment of gut-associated microbiota in the lung correlates with the onset of acute respiratory distress syndrome and long term outcomes. And the ACE2, the receptor of SARS-CoV-2 plays a role in the regulation of microbiota depending on amino acids and antimicrobial peptides. Gut microbiota also enhances the antivirus immunity in a remote region to defend the virus through the enrichment of the virus-specific T cells, decrease immunopathology or stimulate interferon response and in turn, in some cases, the virus also influences the composition of the microbiota. The exploration of microbiota change in SARS-CoV-2 infection may help us to predict the outcome of patients and confer the development of microbe depending treatment.